Toward Quality Control in Precast Concrete Methods: Development and Validation of Inspection Management System - Moon, Jaesang; Seo, Wonseok; Kim, Jinyoung (Journal of the Architectural Institute of Korea, 2024)
The precast concrete (PC) method involves manufacturing components at the factory and assembling them on-site. Effective application of the PC method requires proper quality management of manufactured PC components. Currently, many PC factories conduct inspections on selected PC components and generate paper-based inspection reports due to time and cost constraints. To enhance both the quality and quantity of inspections without increasing time, this study proposed a quality control system that automatically records data and generates inspection reports for PC components. The system includes recording inspection results based on component specifications, storing comprehensive inspection data, and automatically constructing digital inspection reports. The developed system was tested in a PC factory to validate its efficiency. Additionally, a survey was conducted to enhance the system's usability in the field, and the system was updated based on the survey findings.
Keywords: Inspection Report; Precast Concrete Factory; Quality Control; Quality Inspection; System Usability Scale